Answer:
i dont know
Step-by-step explanation:
Answer:
![a=-3](https://tex.z-dn.net/?f=a%3D-3)
Step-by-step explanation:
we have
![a-2=\frac{3+6a}{3}](https://tex.z-dn.net/?f=a-2%3D%5Cfrac%7B3%2B6a%7D%7B3%7D)
Solve for a
That means ----> Isolate the variable a
Factor 3 in the numerator right side
![a-2=\frac{3(1+2a)}{3}](https://tex.z-dn.net/?f=a-2%3D%5Cfrac%7B3%281%2B2a%29%7D%7B3%7D)
Simplify right side
![a-2=1+2a](https://tex.z-dn.net/?f=a-2%3D1%2B2a)
subtract a both sides
![a-2-a=1+2a-a](https://tex.z-dn.net/?f=a-2-a%3D1%2B2a-a)
![-2=1+a](https://tex.z-dn.net/?f=-2%3D1%2Ba)
subtract 1 both sides
![-2-1=1+a-1](https://tex.z-dn.net/?f=-2-1%3D1%2Ba-1)
![-3=a](https://tex.z-dn.net/?f=-3%3Da)
Rewrite
![a=-3](https://tex.z-dn.net/?f=a%3D-3)
The answer is 3x.
Factor out 3x and u get 3x(x-3).
It is 1082.
I hope it helps, you can do more on a calculator. :)))